Potential applications of JAK inhibitors, clinically approved drugs against autoimmune diseases, in cancer therapy - Wei, Xiao-Huan; Liu, Yuan-Yuan (Frontiers in Pharmacology, 2024)
Disturbances in immunoregulation may lead to both cancer and autoimmune diseases. Many therapeutic drugs for autoimmune diseases also display anti-tumor efficacy. The Janus kinase/signal transducer and activator of transcription signaling pathways are involved in the secretion of more than 50 distinct cytokines, which have critical roles in inducing autoimmune diseases and tumorigenesis. Thus, Janus kinases have become classical immunotherapeutic targets for immune disease. More than 70 Janus kinase inhibitors have been approved as immunomodulatory drugs for clinical use, of which 12 are used in the treatment of autoimmune diseases. This systematic review aims to elucidate the antitumor role of clinically approved Janus kinase inhibitors that were primarily designed for the treatment of autoimmune diseases and their potential for clinical translation as cancer treatments.